Efektivitas Media Sosial Whatsapp sebagai Media Pembelajaran Online Mahasiswa Pendidikan Administrasi Perkantoran Unesa pada Mata Kuliah Praktik Administrasi Perkantoran - Ratri Putri Nurjanah; Durinda Puspasari (Edunusa: Journal of Economics and Business Education, 2022)
The study aims to analyze the effectiveness of WhatsApp social media as an online learning media for Unesa Office Administration Education students in office administration practice courses. This research is a descriptive research with a qualitative approach. Data collection techniques were interviews and questionnaires to Unesa Office Administration Education students class 2017. The validity of the data used source triangulation. The data analysis technique uses the Miles and Huberman model, namely data collection, data reduction, data presentation, and conclusions. The results showed that the use of social media whatsapp as an online learning media in office administration practice courses was effective based on three indicators: in terms of intensity, seen from the implementation of online lectures, many were done using whatsapp as a learning media; in terms of communication, from the point of view of lecturers and students taking advantage of the features found on WhatsApp to send and receive lecture materials and assignments in pdf file format, photos, videos and also voice message features; in terms of satisfaction, seen from students who are satisfied because of the fulfillment of information needs during online lectures. Students are helped to distribute lecture materials that have been delivered by lecturers through whatsapp groups. In addition, the whatsapp group also helps students understand the lecture material so that they can complete the tasks given by the lecturer.